Assessment of FOXO4 Gene Expression and Serum Keap-1, Aldolase, IL-18, and IL-22 Levels in Patients with Colorectal Cancer - Lazem, Haneen S.; Sharba, Zahraa A.; Sulaiman, Ghassan M.; Fasial, Zainab H.; Khalil, Khalil A. A.; Ahmed, Elsadig M. (Iraqi Journal of Science, 2025)
Colorectal cancer (CRC) is a prevalent form of cancer worldwide, yet there is a scarcity of research on the serum levels of interleukins (ILs) in patients with CRC, with only a limited number of studies having been published to date. The present work aimed to investigate the contributions of selected blood molecules, namely IL-18 and IL-22, Kelch-like ECH associated protein-1 (Keap-1), aldolase (ALD), and forkhead O4 (FOXO4). The analysis involved 60 CRC patients and30 healthy subjects who served ascontrol. The serum levels of IL-22, IL-18, Keap-1, and ALD were performed by enzyme-linked immunosorbent assay (ELISA), while FOXO4 expression was measured by RT-qPCR. Serum levels of IL-18, IL-22, and Keap-1 were not statistically significant among patients with varying Dukes' stages, tumor sizes, histological grades, and different situations of distant metastasis of cancer cells (P>0.05). While ALD show a highly significant differences between patients and control group (P<0.05)The expression of FOXO4 is down-regulated and was statistically different (P<0.05) in patients with CRC. These findings showed that levels of interleukins in the serum cannot be used as a marker for cancer. However, our results on the ALD enzyme showed a significant elevation in CRC patients in comparison with the healthy subjects, which may have future implications for confirming the incidence of colon cancer.